Involvement of sialoglycans in SARS‐COV‐2 infection: Opportunities and challenges for glyco‐based inhibitors. Issue 12 (19th November 2022) - Kuhaudomlarp, Sakonwan; Imberty, Anne
Abstract: Viral infections have been the causes of global pandemics, including the ongoing coronavirus disease 2019, which prompted the investigation into the infection mechanisms to find treatment and aid the vaccine design. Betacoronaviruses use spike glycoprotein on their surface to bind to host receptors, aiding their host attachment and cell fusion. Protein‐glycan interaction has been implicated in the viral entry mechanism of many viruses and has recently been shown in SARS‐CoV‐2. Here, we reviewed the current knowledge on protein‐glycan interactions that facilitate SARS‐CoV‐2 host entry, with special interest in sialoglycans present on both the virions and host cell surfaces. We also analyze how such information provides opportunities and challenges in glyco‐based inhibitors.